Impact of the COVID-19 pandemic and the Russia-Ukraine war on stress and anxiety in students: A systematic review - Limone, Pierpaolo; Toto, Giusi Antonia; Messina, Giovanni (Frontiers in Psychiatry, 2022)
Background: The outbreak of the COVID-19 pandemic at the end of 2019 and the Russian-Ukrainian war in February 2022 created restrictions and uncertainties that affected the general population's mental health. One of the affected groups was students. This systematic review summarises the current literature on the prevalence, outcomes, and interventions for stress and anxiety among university, college, graduate, or postsecondary populations. Methods: A systematic literature search was performed on PubMed, Web of Science, Scopus, Embase, Cochrane Library, CINAHL, PsychInfo, and ProQuest, following PRISMA guidelines. Specific inclusion and exclusion criteria were applied, and screening was performed to identify the definitive studies. Results: The prevalence of anxiety was relatively high, ranging from 88.9% to 13.63%, and the prevalence of stress ranged from 56% to 28.14%. The predictors of stress and anxiety included young age, gender being female, STEM course, loneliness, low academic level in school, urban lockdown, confinement, having a preexisting disease, having relatives or friends infected with COVID-19, and proximity to a COVID-19 zone. The predictors of stress included gender being female, living with family, living in a household with many people, being confined rather than having the freedom to relocate, proximity to confirmed cases of COVID-19, lack of access to materials on COVID-19, preexisting mental disorders, and lack of knowledge on the preventable nature of COVID-19. The sources of anxiety among the university students identified in the study included academics, postponement of graduation, cancellation or disruption of planned events, inability to achieve goals, and finances. In addition, the students used trauma-focused, forward-focused, task-oriented, emotion-oriented, and avoidance-oriented coping strategies. Conclusion: The included studies showed that stress and anxiety increased during the pandemic and the war, with gender and uncertainty playing a critical role. The studies provide insights into the widespread use of problem-focused and task-focused coping strategies despite their impact on increasing stress and anxiety